(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study examines the portrayal of Corporate Social Responsibility (CSR) initiatives in mass media and their impact on corporate reputation and public perception. Using a descriptive research design, the study analyzes data collected from 362 corporate employees from branded companies. The research focuses on the effectiveness of communication strategies, media influence on CSR efforts, and transparency in CSR communication. Findings reveal that larger companies engage more frequently in CSR activities, perceive media coverage as more impactful, and rate their communication strategies as more effective compared to smaller firms. Transparency and the response to negative media coverage also vary by company size, with larger companies generally showing higher levels of transparency and more proactive responses. The study highlights the nuanced ways in which company size influences CSR practices and media representation.